Evaluasi Ruang Terbuka Hijau Alun-Alun Pondok Aren Berdasarkan Standar dan Persepsi Pengunjung - Jaelani, Ahmad; Febryarini, Lusy; Utami, Tin Budi (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
The availability of green open space in South Tangerang City is currently 7.52%, which falls short of the 20% target set by the central government. To improve the quality of urban facilities, the city plans to construct Pondok Aren Squarety in 2024. However, a thorough evaluation is needed to ensure that the square is built and designed according to standards and meets the expectations and needs of visitors. As part of this effort, a comprehensive evaluation of Pondok Aren Square will be conducted. The study aims to address the challenges faced by local governments in providing 20% of green open space in urban areas, which is crucial for mitigating climate change and achieving the mission of net-zero emissions to develop its urban planning and the construction of Pondok Aren Square is one of the steps taken to improve the quality of urban facilities. This research will take a quantitative approach involving measurements based on relevant standards as well as the collection of visitor perception data.